Gender differences in lower limb frontal plane kinematics during landing - Hughes, G.; Watkins, J.; Owen, N. (Sports Biomechanics, 2008)
The aim of this study was to investigate gender differences in knee valgus angle and inter-knee and inter-ankle distances in university volleyball players when performing opposed block jump landings. Six female and six male university volleyball players performed three dynamic trials each for which they were instructed to jump up and block a volleyball suspended above a net set at the height of a standard volleyball net as it was spiked against them by an opposing player. Knee valgus/varus, inter-knee distance, and inter-ankle distance (absolute and relative to height) were determined during landing using three-dimensional motion analysis. Females displayed significantly greater maximum valgus angle and range of motion than males. This may increase the risk of ligament strain in females compared with males. Minimum absolute inter-knee distance was significantly smaller, and absolute and relative inter-knee displacement during landing significantly greater, in females than males. Both absolute and relative inter-ankle displacement during landing was significantly greater in males than females. These findings suggest that the gender difference in the valgus angle of the knee during twofooted landing is influenced by gender differences in the linear movement of the ankles as well as the knees. Coaches should therefore develop training programmes to focus on movement of both the knee and ankle joints in the frontal plane in order to reduce the knee valgus angle during landing, which in turn may reduce the risk of non-contact anterior cruciate ligament injury.